Kemampuan Guru PAI dalam Mengelola Pembelajaran di MTs Ittihadiyah Laut Dendang, Kecamatan Percut Sei Tuan Kabupaten Deli Serdang - Setiawan, Yuda Wira; Neliwati (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
This study aims to analyze the competencies of Islamic Religious Education (PAI) teachers in managing classroom instruction at MTS Ittihadiyah Jl. Masjid No. 21 Laut Dendang. Using a descriptive qualitative approach, data were collected through observation, interviews, and documentation involving three PAI teachers: Mrs. Kamalliyah, Mrs. Siti Aminah, and Mr. Mainizar. The results revealed that all three teachers demonstrated strong capabilities in independently designing lesson plans, implementing active and contextual teaching strategies, and conducting comprehensive assessments covering cognitive, affective, and psychomotor domains. The evaluation process not only measured learning outcomes but also focused on fostering students‟ religious character. The study recommends the enhancement of teacher competencies, institutional support from madrasahs, and the integration of technology into PAI instruction.